PcG complexes set the stage for epigenetic inheritance of gene silencing in early S phase before replication. - Chiara Lanzuolo; Federica Lo Sardo; Adamo Diamantini; Valerio Orlando (PLoS Genetics)
Polycomb group (PcG) proteins are part of a conserved cell memory system that conveys epigenetic inheritance of silenced transcriptional states through cell division. Despite the considerable amount of information about PcG mechanisms controlling gene silencing, how PcG proteins maintain repressive chromatin during epigenome duplication is still unclear. Here we identified a specific time window, the early S phase, in which PcG proteins are recruited at BX-C PRE target sites in concomitance with H3K27me3 repressive mark deposition. Notably, these events precede and are uncoupled from PRE replication timing, which occurs in late S phase when most epigenetic signatures are reduced. These findings shed light on one of the key mechanisms for PcG-mediated epigenetic inheritance during S phase, suggesting a conserved model in which the PcG-dependent H3K27me3 mark is inherited by dilution and not by de novo methylation occurring at the time of replication.